Ética do encontro - Masetti, Morgana (2018)
This study seeks to investigate which elements favor the quality of the relationship between health professionals and patients in health construction. It is known that medical care protocols do not insure immunity to the suffering of the other: there is always a flow of life waiting to be ushered in. The idea is to conceive devices so that health professionals can foster these flows without expelling them from the relational field, nor annihilate themselves through them, transforming them into living potency when caring of the patient. We live in a society that privileges the medicalization of life, where individualized treatment strengthens a therapeutic way of living. In it, personal fate is not bound to the collective one. Systemic problems are often experienced and treated with solutions to individual problems, generating a feeling of helplessness and indifference towards the other. Public space disappears and is replaced with the various publics that the power devices create and treat in a way that does not foster the creation of unique meanings that such processes could generate. Pain, when it cannot be silenced, poses itself as a borderline experience of the relationship between health professionals and patients. It whispers a new language that invites us to delve into the small cracks, opening different temporalities for the encounter. The encounter in this narrative is thought as a set of possibilities and potentialities present in the space and time of the relationship, minimum existences that may or may not be established. In this sense, the encounter is established in the wealth of what is not defined and cannot be completed but together, a possibility of freedom achieved through the intertwining with the other